Evaluating the appropriateness of platelet transfusions compared with evidence‐based platelet guidelines: An audit of platelet transfusions at 57 hospitals. Issue 1 (20th October 2020) - Hill‐Strathy, MaryJane; Pinkerton, Peter H.; Thompson, Troy A.; Wendt, Alison; Collins, Allison; Cohen, Robert; BComm, Wendy Owens; Cameron, Tracy; Lin, Yulia; Lau, Wendy; Lieberman, Lani; Callum, Jeannie
Abstract: Background: Platelet transfusions are used to prevent or control bleeding in patients with thrombocytopenia or platelet dysfunction. The pretransfusion platelet count threshold has been studied extensively in multiple patient settings yielding high‐quality evidence that has been summarized in several comprehensive evidence‐based platelet guidelines. Study Design and Methods: A prospective 12‐week audit of consecutive platelet transfusions using validated and evidence‐based adjudication criteria was conducted. Patient demographic, laboratory, and transfusion details were collected with an electronic audit tool. Each order was adjudicated either electronically or independently by two transfusion medicine physicians. The aim was to determine platelet transfusion appropriateness and common scenarios with deviations from guidelines. Results: Fifty‐seven (38%) of 150 hospitals provided data on 1903 platelet orders, representing 90% of platelet usage in the region during the time period. Overall, 702 of 1693 adult (41.5%) and 133 of 210 pediatric orders (63.3%) were deemed inappropriate. The most common inappropriate platelet order was for prophylaxis in the absence of bleeding or planned procedure in patients with hypoproliferative thrombocytopenia and a platelet count over 10 x 10 9 /L (53% of inappropriate orders in adults and 45% in pediatrics). Platelet transfusions ordered with either a preprinted transfusion order set (odds ratio [OR], 1.97; 95% confidence interval [CI], 1.44‐2.73) or technologist prospective screening (OR, 1.40; 95% CI, 1.10‐1.78) were more likely to be appropriate. Conclusion: There is a discrepancy between clinical practice and evidence‐based platelet guidelines. Broad educational and system changes will be needed to align platelet transfusion practice with guideline recommendations.